2020
DOI: 10.1111/vox.13024
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion activity in a general hospital during the COVID‐19 pandemic

Abstract: Background The COVID‐19 outbreak has affected almost all hospital departments, including transfusion services. However, the demand for transfusions in a general hospital designated to deal with COVID‐19 patients has not been analysed before. Study Design and Methods A retrospective study was conducted to evaluate blood transfusion practices from 15 March to 14 April 2020 at Hospital Universitario Infanta Leonor (Madrid, Spain). During this month, with few exceptions, the hospital became a ‘COVID‐19’ centre. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Our study is related to other studies reporting a drop in blood during COVID-19 in ICUs of over 50%. Other studies, such as the first one carried out in China and the United States, have shown that 95% of ICU patients had anemia and that 85% of those were admitted to the ICU for seven days or more, which coincides with our study, in which a mean of 9.37 ± 12.03 days in the ICU [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study is related to other studies reporting a drop in blood during COVID-19 in ICUs of over 50%. Other studies, such as the first one carried out in China and the United States, have shown that 95% of ICU patients had anemia and that 85% of those were admitted to the ICU for seven days or more, which coincides with our study, in which a mean of 9.37 ± 12.03 days in the ICU [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…2 Concurrently and also for pandemic-related reasons, hospitals canceled elective surgeries, decreasing blood utilization. 3 By late spring, blood usage returned to historical norms. [4][5][6][7] The ongoing pandemic continued to spur shortages of blood components throughout 2020, 8,9 especially for patient populations with special needs.…”
Section: Introductionmentioning
confidence: 99%
“…During the first quarter of 2020, the COVID‐19 pandemic disrupted blood collections due to cancellations, increased social distancing, and personal protective equipment requirements, 1 leading to blood shortages 2 . Concurrently and also for pandemic‐related reasons, hospitals canceled elective surgeries, decreasing blood utilization 3 . By late spring, blood usage returned to historical norms 4–7 .…”
Section: Introductionmentioning
confidence: 99%
“…This had led to a large reduction in the number of stock inventories and regional donation centers. In several countries, the pattern of decline in voluntary donations was globally well observed despite the tremendous efforts made by health authorities and the media to assure safe practices and precautions to prevent the transmission of infection in the blood donation areas [1,[11][12][13]. The WHO has given a preliminary guidance to maintain a safe and sufficient blood supply during the COVID-19 pandemic [14].…”
Section: Introductionmentioning
confidence: 99%